ENHANCING GRAMMAR PROFICIENCY THROUGH A GAMIFIED SNAKE AND LADDER GAME FOR ELEVENTH-GRADE STUDENTS AT SMAN 1 BATIPUH, WEST SUMATRA - Usman, Nurlatifah; Sujito (Universitas Muhammadiyah Muara Bungo, 2025)
This study aims to investigate the grammar proficiency of eleventh-grade students at SMAN 1 Batipuh, West Sumatra, using a gamification approach. The experimental design used was a single-group pre-test and post-test. The Snakes and Ladders game combines gamification elements such as points, leaderboards, challenge-based progression, and peer collaboration to improve engagement and grammar learning outcomes. Data were collected from 33 students of grade XI F1 SMAN 1 Batipuh. The results showed a statistically significant increase; the pretest and posttest scores were normally distributed, as indicated by the results of the data normality test, with a sig. pretest value of 0.390 and a sig. posttest value of 0.083, each exceeding α (0.05). With a negative value of -21.082 below and -13.766 above, the first hypothesis test showed an effect. If the sig. (2-tailed) value shows a figure of 0.001, which means less than 0.05, then Ho is rejected and Ha is accepted. The results show that grade XI students of SMAN 1 Batipuh, West Sumatra, can improve their grammar skills through gamification-based snakes and ladders games. This study highlights the potential of gamification as an effective pedagogical tool in English language teaching, making grammar teaching more interactive and enjoyable. The findings suggest incorporating structured game mechanisms into learning activities can improve academic performance and student engagement.